Mainstreaming of children's library services at the Sentro ng Karunungan Library, Tayuman, Manila - Romero, Xenia B.; Apolinario, Rhea Rowena U.; Santos, Yhna Therese P. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2019)
Children with special needs are usually neglected and its capability to socially adjust commonly judged by the community. The public library as a venue for their great improvement was never recognized. Public librarian and person-in-charge in the public libraries are hesitant to include them in their children's library services due to their unpredictable behavior and uncontrolled red flags.
The Children's Section of the Sentro ng Karunungan Library provides library services for the typically developing children. This project will discuss how the mainstreaming of children's library services have paved the way of social integration of children with special needs as a regular library user in a public library. A "Special Library Day" will be included in the regular library program of the SKL Children's Section.
Special Problem (Master of Library and Information Science)
Keywords: Children's Library -- Sentro ng Karunungan Library -- Tayuman